Native Surface Oxides Featured Liquid Metals for Printable Self-Powered Photoelectrochemical Device - Wang, Yuqing; Li, Yaqi; Zhang, Jingwei; Zhuang, Jincheng; Ren, Long; Du, Yi (Frontiers in Chemistry, 2019)
Constructing high-performance photo-electrodes by patterning the photo-active semiconducting components with desirable texture and architecture is one of the most promising approaches to achieve the practical and scale-up application of photo-electric or photoelectrochemical (PEC) devices. However, it is a still big challenge to efficiently and effectively handle nano-structural semiconducting materials into intergraded circuit devices, displaying good electric-contact and stability. Here, a facile manufacture strategy for fabricating native metal-oxides based photo-electrodes by directly printing Ga-based liquid metals is explored. The PEC device, functionalized by the native Ga-oxide functional layer, exhibits self-powered photo-detection behaviours and presents fast photo-electric responsibility in response to the simulated Sunlight illumination. This printable PEC device shows good potential for high sensitive self-powered photo-detector and provides a flexible and versatile approach for the design and fabrication of novel electrode structures.